Pulmonary alveolar microlithiasis: a case report - Somocurcio V., Jose G. (2018)
Pulmonary alveolar microlithiasis a rare disease whose main characteristic accumulation of calcium salts within the air cell, this due to the presence of a genetic mutation autosomal recessive. This entity is within the group of diffuse lung diseases and primary diagnosis is a challenge for health professionals. There is no treatment to date, has raised the use of bisphosphonate, steroids and bronchoalveolar lavage without reaching conclusive results. It is preferred to perform the transplant before the development of right ventricular failure for best results. The definitive diagnosis is histopathological. In Peru it has been poorly described this disease as the only report found no definitive histopathological diagnosis. We report a case diagnosed in the Department of Thoracic and Cardiovascular Surgery Hipolito Unanue National Hospital in Lima, Peru.